Potensi Senyawa Bioaktif Ekstrak Kasar Bakteri Simbion Spons sebagai Anthelmintika : Sebuah Uji Pendahuluan - Muhammad Reza Faisal; Mujizat Kawaroe; Fadjar Satria (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2014)
This study aims to observe the bacterial symbionts of sponge and determine chemical compounds profile in the crude extract of bacterial isolates then to determine the lethal toxicity values (LC50-24 hours) as a preliminary anthelmintic test. The method consisted of the identification of gram staining, organic solvent extraction, phytochemical screening and toxicity assay by the Artemia salina LC50-24 hours. The concentration used consisted of 10 µg / ml; 100 µg / ml; 250 µg / ml; 500 µg / ml. Results showed isolate SC12 (2) C and S1-2 (1) belonging to the gram-positive where the bioactive compounds i.e. flavonoids and triterpenoids obtained from the crude extract were predominant. The minimum concentrations from toxicity tests were 35.11 µg/ml for isolate SC12(2)C and 41.2 µg/ml for S1-2 (1). The crude extract of both isolates showed potential as a anthelmintic compound with concentration LC50-24 hours <1000 mg/ml.Keywords : Bacterial symbionts sponge, S12(2) C, S1-2 (1), Phytochemicals, toxicity, Anthelmintic.